Analisis Kesulitan Belajar Bahasa Arab dalam Keterampilan Menulis pada Siswa Kelas VII MTs Hifzhil Qur’an Islamic Centre Medan - Hafisah Perangin-Angin; Harun al Rasyid (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This article explains the analysis of difficulties in writing skills (Mahârah al-kitâbah) in class VII students at Mts Hifzhil Qur'an Islamic Center Medan. The purpose of this research is to analyze what difficulties students are experiencing in learning Arabic regarding writing skills. This research uses a qualitative method with a descriptive approach. Descriptive research intends to analyze, define and obtain facts based on a certain perspective or state of mind. To obtain information, researchers used data collection procedures through observation, interviews, and documentation. The findings from this research show that students' difficulties in learning Arabic writing skills are influenced by five factors consisting of internal and external factors, namely, first, the students' lack of memorizing Arabic vocabulary. second, the lack of student interest in learning Arabic. Third, students come from various different elementary school educational backgrounds. Fourth, there are guidebooks for learning Arabic that do not suit students' abilities, and fifth, there is no special method for students to practice writing Arabic. From the writing that researchers have written, this can be an example in learning Arabic for students' writing skills, and can provide new insights in developing more effective learning.